2016
DOI: 10.1007/s00234-016-1741-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of preoperative dynamic contrast-enhanced MRI perfusion parameters for high-grade glioma patients

Abstract: IntroductionThe prognostic value of the dynamic contrast-enhanced (DCE) MRI perfusion and its histogram analysis-derived metrics is not well established for high-grade glioma (HGG) patients. The aim of this prospective study was to investigate DCE perfusion transfer coefficient (Ktrans), vascular plasma volume fraction (vp), extracellular volume fraction (ve), reverse transfer constant (kep), and initial area under gadolinium concentration time curve (IAUGC) as predictors of progression-free (PFS) and overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 55 publications
3
46
1
Order By: Relevance
“…This correlation might indicate that GBM aggressiveness is associated with a high angiogenic capacity. These results are consistent with the consideration of perfusion markers among the most consistently recognized independent predictors of survival and glioma grade progression …”
Section: Introductionsupporting
confidence: 86%
“…This correlation might indicate that GBM aggressiveness is associated with a high angiogenic capacity. These results are consistent with the consideration of perfusion markers among the most consistently recognized independent predictors of survival and glioma grade progression …”
Section: Introductionsupporting
confidence: 86%
“…K trans has been positively correlated with tumor grade, although the direct relationship between K trans and prognosis is unclear. Several studies have found that K trans is associated with worse progression‐free and overall survival, while one study found the opposite and another study found no correlation . k ep represents the rate of flow from the extravascular space into the plasma.…”
Section: Discussionmentioning
confidence: 97%
“…Data on the role of k ep are limited. While one study found k ep to be a positive prognostic factor for overall survival, 30 another study found the opposite relationship, and found k ep to be a strong predictor of matrix metalloproteinase 9 expression. 31 Our findings of higher K trans and k ep predicting poorer overall survival in only the TERT-mutated group suggest that the relationship between survival and permeability may be more tightly coupled in the presence of TERT mutation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations